Modern media in teaching music: Didactic specifics and potentials - Ivanović Marija K. (University of Kragujevac - Faculty of Pedagogy, Užice, 2019)
The paper discusses the phenomenon of modern media today, as well as the possibility of their application in education, with particular reference to the technologies and potential of the Internet, social networks and applications in teaching music and learning musical contents. There was talk about didactic specifics and potentials of modern media in teaching music and how they can be integrated into teaching music. The aim of the paper is to provide an overview of the modern media that can serve the development and improvement of the quality of music education.